The challenge of transforming urban supply and disposal infrastructures to more resource and energy efficiency. - Lehn, Helmut; Steiner, Franka; Friedrich, Jasmin; Araya Valenzuela, Dámare (My University, 2018)
Facing global climate change, the transformation of energy systems in many countries of the world has already been progressed significantly. In line with this development, a shift towards closed loops has been iniciated in some parts of the world by separating urban solid wastes for recycling purposes. In contrast, the more than 5.000 year tradition of urban water supply and urban waste water discharge seems to be without any alternative: cities import fresh water from their hinterlands and flush the sewage to areas situated downstream in order to avoid the appearance of epidemics. This longlasting practice was supplemented by stepwise adding end-of-the pipe technologies of sewage treatment from the early 20th century on. Now in many parts of Europe three treatment stages are standard. The current debate in some European countries about a forth and even fifth stage rise the question whether this development of adding more and more treatment stages to the old sewer pipe technology can be assessed as sustainable with respect to resources and energy consumption on one hand and impacts on the environment on the other hand. During the last 20 years new and innovative infrastructure systems for water supply and waste water management have been developed and implemented on a pilot scale. Most of the associated technologies make use of the separate collection and treatment of specific waste water streams. The separate handling of these different streams requires physical modifications but also challenges behavorial patterns and institutional frameworks. Therefore, investigation is necessary to know how the implementation of these technologies can be made more convenient in order to achieve a significantc impact on the urban sustainability performance.
Keywords: Energieeffizienz; Infrastruktur; Abwasserentsorgung; Abwasserleitung; Nachhaltigkeit